2018
DOI: 10.1002/jat.3764
|View full text |Cite
|
Sign up to set email alerts
|

Maternal di‐(2‐ethylhexyl) phthalate exposure alters hepatic insulin signal transduction and glucoregulatory events in rat F1 male offspring

Abstract: Di‐(2‐ethylhexyl) phthalate (DEHP) is a commonly used plasticizer with endocrine disrupting properties. Its widespread use resulted in constant human exposure including fetal development and postnatal life. Epidemiological and experimental data have shown that DEHP has a negative influence on glucose homeostasis. However, the evidence regarding the effect of maternal DEHP exposure on hepatic glucose homeostasis is scarce. Hence, we investigated whether DEHP exposure during gestation and lactation disrupts gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…A broad range of early-life environmental chemical exposures have been related to increased risk for developing hypertension of developmental origins, as we reviewed elsewhere [94]. These chemicals, di-(2-ethylhexyl) phthalate (DEHP) and bisphenol A, have been studied for their impact on insulin resistance in adult progeny [63,65]. These findings are in agreement with epidemiological research data showing that endocrine-disrupting chemical exposure is linked to CVDs later in life [95].…”
Section: Chemical and Medication Exposuressupporting
confidence: 73%
“…A broad range of early-life environmental chemical exposures have been related to increased risk for developing hypertension of developmental origins, as we reviewed elsewhere [94]. These chemicals, di-(2-ethylhexyl) phthalate (DEHP) and bisphenol A, have been studied for their impact on insulin resistance in adult progeny [63,65]. These findings are in agreement with epidemiological research data showing that endocrine-disrupting chemical exposure is linked to CVDs later in life [95].…”
Section: Chemical and Medication Exposuressupporting
confidence: 73%
“…Prior review showed adult rats exposed to several chemicals during early life developed hypertension, a major feature of MetS [ 78 ]. These chemicals, while only bisphenol A and di-(2-ethylhexyl) phthalate (DEHP), have shown their programming effects resulting in insulin resistance in adult progeny [ 79 , 80 ].…”
Section: Current Evidence Supports Mets Of Developmental Originsmentioning
confidence: 99%
“…Studies with endocrine-disrupting chemicals show that they activate gluconeogenesis abnormally through the activation of enzymes involved in gluconeogenesis in the liver. It is also known that glucose uptake in tissues decreases as a result of exposure to endocrine disruptors (Rajagopal et al, 2019a(Rajagopal et al, , 2019b. So, exposure to MeP+PrP may have directly affected glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%